Semiotic Analysis of Cultural Representation of Documentary Films of The Osing Banyuwangi Tribe - Haekal Ridho Afandi (Universitas Muhammadiyah Sidoarjo, 2023)
The research objective is to package about cultural preservation related to tradition through its power, which is able to form images and sounds that can be understood by the audience to describe and explain the meaning contained in the communicative message of the Osing Tribe in Banyuwangi through native language dialectics. This research method is descriptive qualitative using Roland Barthes's semiotic approach. The data collection process was carried out through primary data resulting from scene cuts and scenes from films added to secondary library data as supporting primary data adapted from the cultural traditions of the Osing Tribe in Banyuwangi. The results obtained in this research are the emergence of findings, namely: 1). Giving a correlation to the influence of the meaning that appears has a communicative message in the cultural and language traditions of the Osing Tribe which are related to the identity and characteristics that exist in an area. 2). Expanding the reach of the community on a village scale to a larger and more relevant context in a modern state and regionally administratively becomes the starting point and also the framework for the process of creating an identity.